Green Polymer Nanocomposites for Skin Tissue Engineering - Shokrani, Hanieh; Shokrani, Amirhossein; Jouyandeh, Maryam; Seidi, Farzad; Gholami, Fatemeh; Kar, Saptarshi; Munir, Muhammad Tajammal; Kowalkowska-Zedler, Daria; Zarrintaj, Payam; Rabiee, Navid; Saeb, Mohammad Reza (ACS applied bio materials, 2022)
Fabrication of an appropriate skin scaffold needs to meet several standards related to the mechanical and biological properties. Fully natural/green scaffolds with acceptable biodegradability, biocompatibility, and physiological properties quite often suffer from poor mechanical properties. Therefore, for appropriate skin tissue engineering and to mimic the real functions, we need to use synthetic polymers and/or additives as complements to green polymers. Green nanocomposites (either nanoscale natural macromolecules or biopolymers containing nanoparticles) are a class of scaffolds with acceptable biomedical properties window (drug delivery and cardiac, nerve, bone, cartilage as well as skin tissue engineering), enabling one to achieve the required level of skin regeneration and wound healing. In this review, we have collected, summarized, screened, analyzed, and interpreted the properties of green nanocomposites used in skin tissue engineering and wound dressing. We particularly emphasize the mechanical and biological properties that skin cells need to meet when seeded on the scaffold. In this regard, the latest state of the art studies directed at fabrication of skin tissue and bionanocomposites as well as their mechanistic features are discussed, whereas some unspoken complexities and challenges for future developments are highlighted.
Keywords: polymery; Nanocomposites; Polymers; Biocompatible Materials; tkáňové inženýrství; Tissue Engineering; nanokompozity; skin tissue engineering; Hydrogels; biomaterials; biological properties; bionanocomposites; biokompatibilní materiály; green nanocomposites; hydrogely; mechanical properties